(untitled) (Research, Society and Development, 2022)
This integrative review aims to analyze scientific articles that relate the use of botulinum toxin type A in the treatment of sialorrhea in patients in Intensive Care Units. For this study, the descriptors were used: Botulinum Toxins Type A; Botulinum Toxins; Muscular Dystrophies; Muscular Dystrophy; Diseases of the Autonomic Nervous System; Intensive treatment unit; Intensive Care Units. The databases accessed were: PUBMED and MEDLINE. The collection followed 5 stages. First, the theme related to the objectives; second according to determination of inclusion/exclusion criteria; third collection and stratification of information; fourth evaluation of methods; fifth interpretation of results, discussion and conclusion. Of these, 100 articles were identified, those that did not meet the eligibility criteria were excluded and only 10 articles were selected for the study. The delimitation of the research clipping began in 2016, until the end of 2022. The use of botulinum toxin type A in the treatment of sialorrhea in the ICU, respects comparative criteria between objective, thematic associations and conclusions; according to the sequence: Authors/year/study design, objectives/correlations and associations/conclusions. In conclusion, TXB type A may be a bedside therapy option in patients with sialorrhea. TXB type A is effective and has rare side effects, improving the clinical status of patients. This review reveals the need for further experimental studies to justify the use of type A TXB in the protocol treatment of sialorrhea in patients with various neuromuscular diseases in the Intensive Care Unit.